CRIMINAL ACT OF CORRUPTION IN THE CONSTRUCTION OF THE WALEMPING RIVER BRIDGE, BARRU REGENCY - Andi Harahap; Sunardi Purwanda; Khaerul Mannan; Bakhtiar Tijjang; Muhammad Sabir (RADJA PUBLIKA, 2026)
This study aims to determine and analyze the application of the elements of the criminal act of corruption to the legal facts revealed in the trial of the Walemping River Bridge construction case based on Decision Number 42 / Pid.Sus-TPK / 2025 / PN Mks and to determine and analyze the legal basis for the judge's considerations in assessing state financial losses and determining the amount of punishment for the Defendant. This study uses a normative legal research type, with a case study approach to the Legal Analysis of the Corruption Crime in the Construction of the Walemping River Bridge in Barru Regency. The types and sources of legal materials use primary legal materials, secondary legal materials and tertiary legal materials. Data analysis is examined from a qualitative perspective. The results of the study show: 1) That the application of the elements of the criminal act of corruption to the legal facts revealed in the trial of the Walemping River Bridge construction case based on Decision Number 42 / Pid.Sus-TPK / 2025 / PN Mks has been effective. 2) That the basis for the judge's considerations in assessing state financial losses and determining the amount of punishment for the Defendant is by using the judge's legal logic, where in this decision it shifts from formal positivism (looking at what is written in the contract) to pragmatic/material positivism (looking at the facts of where the money flows and what the results are in the field).